Zest Efficacy and Crop Response in Two Acetolactase Synthase-Tolerant Grain Sorghum Hybrids - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
Two ALS-tolerant grain sorghum hybrids were evaluated for efficacy and crop tolerance to Zest (nicosulfuron). Weed control and crop response in two herbicide-tolerant sorghum hybrids were similar. All herbicides controlled kochia, common sunflower, velvetleaf, and quinoa well. Palmer amaranth control was inadequate when no preemergence (PRE) herbicide was applied. Puncturevine and green foxtail control was 90% or more with all Zest (nicosulfuron) treatments applied early postemergence (EPOST) or postemergence (POST). Sorghum injury from the Zest treatments was minor and transient. Relative to the untreated controls, grain yields were greater when a PRE or PRE followed by POST program was used. However, sorghum receiving an EPOST treatment alone yielded no better than the weedy checks.
Keywords: herbicide-resistant sorghum